Las identidades profesionales de los profesores y los perezhivaniya en la adopción de la enseñanza de idiomas asistido por tecnología: Un enfoque longitudinal de la metodología Q - Qin, Lili; Niu, Baogui (Porta Linguarum Revista Interuniversitaria de Didáctica de las Lenguas Extranjeras, 2025)
This study examined the emotional experiences of 13 Japanese-as-foreign-language teachers, using Vygotskian concept of “perezhivanie” in the context of technology-assisted language teaching (TALT) at a northeastern Chinese university. Employing a longitudinal Q Methodology the research tracks the evolution of their professional identities as they engage with TALT over 15 months. Analysis reveals two main professional identities initially – the “advocate of online teaching” and the “supporter of offline teaching”. However, a new identity, the “regretter”, emerges in the second phase, reflecting a sense of missed opportunities in contributing to online course development. By examining educators’ professional identities through perezhivanie, this study highlights the dynamics between their cognitive processes, emotional responses, and technology shaping teacher professional identity within the evolving landscape of TALT.